PROGRAM STUDI HUBUNGAN INTERNASIONAL: BAGAIMANA MENGGAPAI KOMPETENSI DAN AKTUALITAS? - V.L. Sinta Herindrasti (Sociae Polites, 2011)
AbstractIntegration and interdependent among nations has already creating the new world for theIndonesian youth. The on going radical and rapid changing must be anticipated throughthe mind set changing in order to understand deeply how the different sectors of societyhave their own logic of operation and interests. Besides mastering on the basic theoreticalconcepts, the International Relations student must also be equipped with the strong softand hard skills, which are needed to be involved in the global environment so thatInternational Relations Study majoring in various certain fields of study will become a partof efforts to achieve international competence and to answer further more importantquestion, how can we create a transformative social knowledge for our own nationdevelopment?Keywords: Globalization, Linkage, Soft skill, Hard skill, International competence,Transformative social knowledge